Relation of subacute stent thrombosis and resistance to acetylsalicylic acid and clopidogrel in patients with acute coronary syndrome. Insights from the ANIN Myocardial Infarction Registry - Pręgowski, Jerzy; Przyłuski, Jakub; Karcz, Maciej; Norwa-Otto, Bożena; Kruk, Mariusz; Kalińczuk, Łukasz; Tyczyński, Paweł; Ciszewski, Michał; Rużyłło, Witold; Sitkiewicz, Dariusz; Witkowski, Adam (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2010)
Background : Stent thrombosis (ST) is a catastrophic complication of percutaneous coronary interventions (PCI). Aim : To assess the relation between subacute ST and response to antiplatelet treatment in patients with acute coronary syndrome (ACS) and to check the effect of doubling the maintenance dose of clopidogrel on platelet response. Material and methods : We performed a retrospective search of the prospective single-centre ANIN Myocardial Infarction Registry and enrolled 22 patients with a history of subacute ST following PCI for ACS and 36 matched control subjects. Platelet aggregation was assessed at baseline under monotherapy with acetylsalicylic acid (ASA) 75 mg and after 7 days of dual therapy with ASA and clopidogrel 75 mg daily. Platelet function was evaluated with light transmittance aggregometry after addition of an agonist: epinephrine (30 µmol/l) or adenosine 5’-diphosphate (ADP) (5 µmol/l). Patients in whom clopidogrel resistance was identified were administered a maintenance dose of 150 mg and after 7 days platelet aggregation was assessed again. Results : Maximal epinephrine-induced aggregation in patients on ASA who developed ST and in control subjects was similar (48.9 ±28.3% vs. 46.9 ±29.9%, p = 0.8). After 7 days of clopidogrel treatment no significant difference in the extent of aggregation was detected between the study groups (58.7 ±21.3% vs. 66.0 ±17.7%, p = 0.2). According to the binary definition 14% of patients were resistant to ASA in the ST group and 29% of patients in the control group (p = 0.7). Also there was no difference in the incidence of clopidogrel resistance (57% vs. 48%, p = 0.4 respectively). In 13 patients resistant to clopidogrel a dual maintenance dose (150 mg daily) resulted in significant reduction of maximal ADP-induced aggregation after 7 days (73.6 ±16.7% vs. 60.2 ±11.3%, p = 0.037) Conclusions : Clinical and angiographic variables other than laboratory identified platelet resistance to ASA and clopidogrel may play a more important role in the development of subacute stent thrombosis in patients treated with PCI for ACS. Doubling the maintenance dose of clopidogrel may reduce the incidence of platelet resistance.